Treatment of retained placenta with misoprostol: a randomised controlled trial in a low-resource setting (Tanzania) - Fauteck Heiner; Pembe Andrea B; van Beekhuizen Heleen J; Lotgering Fred K (BMC, 2009)
Abstract Background Retained placenta is one of the common causes of maternal mortality in developing countries where access to appropriate obstetrical care is limited. Current treatment of retained placenta is manual removal of the placenta under anaesthesia, which can only take place in larger health care facilities. Medical treatment of retained placenta with prostaglandins E1 (misoprostol) could be cost-effective and easy-to-use and could be a life-saving option in many low-resource settings. The aim of this study is to assess the efficacy and safety of sublingually administered misoprostol in women with retained placenta in a low resource setting. Methods Design: Multicentered randomised, double-blind, placebo-controlled trial, to be conducted in 5 hospitals in Tanzania, Africa. Inclusion criteria: Women with retained placenta, at a gestational age of 28 weeks or more and blood loss less than 750 ml, 30 minutes after delivery of the newborn despite active management of third stage of labour. Trial Entry & Randomisation & Study Medication: After obtaining informed consent, eligible women will be allocated randomly to the treatment groups using numbered envelopes that will be randomized in variable blocks containing identical capsules with either 800 microgram of misoprostol or placebo. The drugs will be given sublingually. The women, maternal care providers and researchers will be blinded to treatment allocation. Sample Size: 117 women, to show a 40% reduction in manual removals of the placenta (p = 0.05, 80% power). The randomization will be misoprostol: placebo = 2:1 Primary Study Outcome: Expulsion of the placenta without manual removal. Secondary outcome is the number of blood transfusions. Discussion This is a protocol for a randomized trial in a low resource setting to assess if medical treatment of women with retained placenta with misoprostol reduces the incidence of manual removal of the placenta. Clinical Trial Registration Current Controlled Trials ISRCTN16104753